2017
DOI: 10.1177/1075547017715473
|View full text |Cite
|
Sign up to set email alerts
|

Improving Climate Change Acceptance Among U.S. Conservatives Through Value-Based Message Targeting

Abstract: Although prior research has identified communication strategies for reducing climate change skepticism, recent research suggests such approaches can backfire. To explore this issue, we report on a preliminary study investigating two prominent messaging styles: consensus and targeted messages. While consensus messaging did not produce significant effects, targeted messages emphasizing free market solutions to climate change were effective at improving conservatives’ climate change acceptance. Furthermore, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
98
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(103 citation statements)
references
References 24 publications
2
98
3
Order By: Relevance
“…Subjects who were told that "97% of climate scientists have concluded that human-caused climate change is happening" did increase their estimates of the "percentage of climate scientists [who] have concluded that human-caused climate change is happening." But consistent with the result in Dixon, Hmielowski and Ma [2017] and Deryugina and Shurchkov [2016], the degree to which those subjects increased their "support for public action" -2 points on a 101-point scale -was not significant, in statistical or practical terms, compared to the responses of the VLFM control group subjects.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Subjects who were told that "97% of climate scientists have concluded that human-caused climate change is happening" did increase their estimates of the "percentage of climate scientists [who] have concluded that human-caused climate change is happening." But consistent with the result in Dixon, Hmielowski and Ma [2017] and Deryugina and Shurchkov [2016], the degree to which those subjects increased their "support for public action" -2 points on a 101-point scale -was not significant, in statistical or practical terms, compared to the responses of the VLFM control group subjects.…”
Section: Resultssupporting
confidence: 71%
“…169-172], a result also reported by Bolsen and Druckman [2017]. The reported VLFM finding would also be in direct conflict with Dixon, Hmielowski and Ma [2017], who found that exposing subjects to a 97%-consensus message had no significant effect; and with Deryugina and Shurchkov [2016], who found that the immediate impact of a consensus message on beliefs in human-caused climate change did not translate into greater support for climate mitigation policies -either immediately or in a six-month follow up study, in which subjects' beliefs in human-caused climate change no longer differed significantly from their pre-message beliefs.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…They seek out and absorb information from experts that share their cultural predispositions (Kahan et al, 2011). Other scholars have shown that resistance to climate science is, to some degree, rooted in opposition to regulation, and that by shifting discourse to emphasize market-friendly solutions to mitigation we can lower conservative resistance to climate science (Campbell & Kay, 2014;Dixon et al, 2017). The implication of this line of research is that we might be able to reduce polarization by framing debates or proposing solutions in ways that are compatible with conservative values.…”
mentioning
confidence: 99%